2013
DOI: 10.1021/ac302826a
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Glycan Detection on Specific Glycoproteins by Lectin Multimerization

Abstract: Improved methods for studying glycans could spur significant advances in the understanding and application of glycobiology. The use of affinity reagents such as lectins and glycan-binding antibodies is a valuable complement to methods involving mass spectrometry and chromatography. Many lectins, however, are not useful as analytic tools due to low affinity in vitro. As an approach to increasing lectin avidity to targeted glycans, we tested the use of lectin multimerization. Several biotinylated lectins were li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 51 publications
(87 reference statements)
1
20
0
Order By: Relevance
“…We speculate that heparan sulfate may sterically interfere with glycan interaction with the lectins used in this study. The performance of lectin affinity capture enrichment in this workflow may be improved by including additional immobilized lectins in the resin mixture whose specificities widen the array of recognized glycan epitopes [57] and/or through the use of lectin multimerization [58]. Unique features of the enrichment methods indicate their suitability for a particular application.…”
Section: Considerations In the Choice Of Gpi-ap Enrichment Strategymentioning
confidence: 99%
“…We speculate that heparan sulfate may sterically interfere with glycan interaction with the lectins used in this study. The performance of lectin affinity capture enrichment in this workflow may be improved by including additional immobilized lectins in the resin mixture whose specificities widen the array of recognized glycan epitopes [57] and/or through the use of lectin multimerization [58]. Unique features of the enrichment methods indicate their suitability for a particular application.…”
Section: Considerations In the Choice Of Gpi-ap Enrichment Strategymentioning
confidence: 99%
“…These limitations have recently been addressed through synthetic efforts focused on developing materials with clustered oligosaccharides to achieve multivalent, high-avidity binding [ 7 , 8 ]. Other reports have demonstrated that clustering lectins together on surfaces also improves lectin avidity towards complementary glycoproteins, thereby improving detection sensitivities [ 9 ]. Using this methodology, we recently developed cell capture surfaces containing three-dimensional, circular films of a block copolymer, poly(glycidyl methacrylate)- block -4,4-dimethyl-2-vinylazlactone) (PGMA- b -PVDMA).…”
Section: Introductionmentioning
confidence: 99%
“…Single‐step addition may enable enhanced binding through multivalent interactions. Thus, the multimerization method can potentially broaden the range of glycan structures that can be detected and provide more and different information compared to monomeric detection . Because of low background labeling and signal amplification, the indirect labeling methods have advantages of high specificity and sensitivity.…”
Section: Factors Influencing Lectin Microarrays For Biomarker Discoverymentioning
confidence: 99%